Direct Coupling of PEM Fuel Cell to Supercapacitors for Higher Durability and Better Energy Management1. Issue 3 (19th April 2018) - Gérardin, K.; Raël, S.; Bonnet, C.; Arora, D.; Lapicque, F.
Abstract: A single polymer electrolyte fuel cell has been directly hybridized to a stack of three supercapacitors: the system formed has been investigated in operation in the fuel cell dynamic load cycle, which emulates the energy demand in transported applications. Comparison with regular, non‐hybridized fuel cell operation was analyzed in terms of hydrogen consumption in the case that the gas flow rates are directly controlled by cell current during the cycles with constant gas stoichiometric factors: the smoothening effect of the supercapacitors in the overall circuit leads to more even profiles of the cell current and voltage in the cycle, which allows safer and better hydrogen consumption management in this regime: the average H2 consumption per cycle could be reduced by 16% without change of the overall energy produced. Besides, the runs were conducted over more than 1, 300 hours with evaluation of the fuel cell performance and capacity at regular intervals, with or without hybridization. A moderate positive effect of hybridization was observed in the time variations of the voltage‐current curves and the fuel crossover. However, the resistances for ohmic, charge transfer and diffusion phenomena, were not so much improved by the hybridization, in spite of less sharp voltage.